Who am I, really? Reflections on developing professional identity as a Cégep teacher - McDonnell, Maggie (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2022)
In this MJE Forum, the author invites conversation on what it means to be a teacher in Quebec’s unique Cegep system. Cegep, positioned between the more structured secondary program and the more autonomous university experience, requires that its teachers grapple with what it means to be a Cegep teacher. Her own piece focuses on exploring her development as a teacher and how teacher identity is shaped by personal and professional relationships. Beyond professional development in workshops and continuing education, Cegep teachers engage in discussions, debates, and collaborations with our peers; ultimately, this community of practice is an essential element in the development of our teaching practice and our identity.